Muscular adaptations to computer-guided strength training with eccentric overload - Friedmann-Bette, Birgit; Kinscherf, Ralf; Vorwald, Silke; Borisch, Stefan; Richter, Götz Martin; Bärtsch, Peter (Acta physiologica Scandinavica, 2004)
Aims:  In order to investigate the muscular adaptations to a novel form of strength training, 18 male untrained subjects performed 4 weeks of low resistance-high repetition knee extension exercise. Methods:  Nine of them trained on a conventional weight resistance device (Leg curler, CON/ECC group), with loads equivalent to 30% of the concentric one-repetition maximum (1RM) for both the concentric and eccentric phase of movement. The other nine trained on a newly developed computer-driven device (CON/ECC-OVERLOAD group) with the concentric load equivalent to 30% of the concentric 1RM and the eccentric load equivalent to 30% of the eccentric 1RM. Results:  Training resulted in significantly (P ≤ 0.05) increased peak torque and a tendency (P = 0.092) to increased muscle cross-sectional area for the CON/ECC-OVERLOAD but not the CON/ECC group, while strength endurance capacity was significantly (P ≤ 0.05) increased in the CON/ECC group only. RT-PCR revealed significantly increased myosin heavy chain (MHC) IIa and lactate dehydrogenase (LDH) A mRNAs, a tendency for increased MHC IIx mRNA (P = 0.056) and high correlations between the changes in MHC IIx and LDH A mRNAs (r = 0.97, P = 0.001) in the CON/ECC-OVERLOAD group. Conclusions:  These results indicate a shift towards a more type II dominated gene expression pattern in the vasti laterales muscles of the CON/ECC-OVERLOAD group in response to training. We suggest that the increased eccentric load in the CON/ECC-OVERLOAD training leads to distinct adaptations towards a stronger, faster muscle.